Designing A Booklet of Local Folktales to Support Junior High School Students English Extensive Reading Activity - Kasangke, Gaela; Ikhsanudin, Ikhsanudin; Suhartono, Luwandi (FKIP - Universitas Tanjungpura, 2025)
This research was aimed to design a booklet of local folktales to support junior high school ninth grade students English extensive reading activities as well as to help them to reach their reading objectives in classroom with the related reading topic. This research was a subject of an English teacher. The method used for this research was development research that used the first three phases of the ADDIE instructional model, namely the analysis, design, and development phases. We conducted the first interview, followed by documentation and observation to gather the data and used experts